Chumchon khemkh̄æng : botrīan phāk patibat - Somphan Tēchaʻathik (Khana Kammakān Prasānngān ʻOngk̨̄on ʻĒkkachon Phatthanā Chonnabot Phāk ʻĪsān : Sāisong Sưksit, Khlet Thai čhatčhamnāi, 1998)
Contributed articles on rural community development with reference to participation of Non-governmental organizations in Northeastern Thailand.